Teletrabalho: um estudo das percep????es do teletrabalhador - Fl??rio, Alice Flora Madeira Ribeiro (2004)
The objective of this research is to analyze the perception of the teleworker about the advantages and disadvantages of his type of work. More specifically the study investigates the following variables: satisfaction, productivity, flexibility, organization, motivation, autonomy, control, stress, relationship with social an family life and isolation. Moreover, the methods employed in the research were the bibliographic review and in depth interviews. The sample was composed by 12 people who were chosen by the convenience method. The analysis was undertaken by interpreting the interviewees speeches. The results revealed that there are many similarities with the aspects pointed in the literature review. However, three dimensions, motivation, satisfaction and quality of life were strongly mentioned by the participants.